Effects of COVID-19 on Pregnancy - Inaam Faisal Mohammed; Rukaia Hassan Abass; Ahmed Khalis Jasim (Academic International Journal of Medical Sciences, 2024)
Background: The COVID-19 pandemic has profoundly impacted pregnant women worldwide. Initial reports suggested pregnancy did not increase severe COVID-19 risk, but emerging data indicate pregnant women may be uniquely vulnerable. This review synthesizes current evidence on COVID-19's effects on pregnant women and their infants.Methods: A literature search was conducted in PubMed, Embase, and Scopus using keywords related to COVID-19 and pregnancy. Original research articles published through January 2023 examining effects of COVID-19 on pregnant women and neonates were included. Study quality was assessed using standardized criteria.Results: 59 studies met inclusion criteria (n=19,164 pregnant women with COVID-19). Compared to non-pregnant controls, pregnant women had higher odds of ICU admission (OR 1.62, 95%CI 1.33-1.96), mechanical ventilation (OR 1.88, 95%CI 1.36-2.60), and mortality (OR 1.62, 95%CI 1.33-1.96). Preterm birth was more likely (OR 1.47, 95%CI 1.14-1.91). Vertical transmission was uncommon (2.7%, 95%CI 1.73-4.21%). SARS-CoV-2 was detected in placenta (17%), amniotic fluid (5.7%), umbilical cord blood (5.8%), and breast milk (13%). Long-term data remain limited.Conclusions: Pregnant women are at increased risk of severe maternal outcomes from COVID-19 compared to non-pregnant women. Preterm birth is more likely. Vertical transmission occurs but appears rare. SARS-CoV-2 can be present in fetal compartments and breast milk. Further high-quality studies are urgently needed to optimize management and mitigate COVID-19 effects on maternal and child health.
Keywords: Covid-19, Pregnancy, pandemic